Karakteristik dan Model Pendidikan Bagi Anak Tunadaksa - Santi, Cinci Oktima; Septiyana, Rindang; Asvio, Nova (PPSDP Undergraduate Journal of Educational Sciences, 2024)
Education of children with special needs, especially children with physical disabilities, is an important matter that requires special attention. Children with physical impairments experience physical limitations in their limbs, making it difficult for them to move and interact socially. This article highlights the importance of education for children with physical impairments to help them overcome physical limitations and obtain a proper education. The research method uses literature study to present information about the characteristics, educational models, and implementation of education for children with physical impairments. Even though they are often considered to lack potential, children with physical impairments can develop their potential through adaptive physical education and special education models. Special and inclusive schools provide special services to meet the needs of children with special needs, including children with physical impairments. The importance of an approach that is appropriate to the needs of children with physical impairments emphasizes the right of every child to receive a proper education. The literature study method applied in this research provides a solid theoretical basis through a review of various related literature. This allows identification of unique characteristics of children with physical impairments as well as effective educational models. This research highlights that, although children with physical disabilities are often thought to have limited potential, they can achieve significant development through adaptive physical education and special education models tailored to their needs.